2022
DOI: 10.1167/iovs.63.1.39
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rat Model of Dry Eye Induced by Aerosol Exposure of Particulate Matter

Abstract: Purpose The purpose of this study was to introduce a novel dry eye rat model induced by aerosol exposure of particulate matter (PM). Methods A total of 30 female Sprague Dawley (SD) rats divided into 3 groups: the control group, the low-level exposed group, and the high-level exposed group. The rats in the experience groups were directly exposed to PM samples in the exposure chamber over 14 days. The clinical observation, including tear volume, corneal fluorescein stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
1
17
1
Order By: Relevance
“…However, when we examined the effects of PM 10 exposure (500 μg/m 3 in a whole body exposure chamber) on tear secretion, no significant change in tear volume was observed after 2 weeks of exposure. Our results also differ from a recent study in female rats exposed to PM in an exposure chamber (500 μg/m 3 for 2 weeks) that showed a significant reduction in tear volume after 14 days [ 48 ]. These differences could be due to the type of particulates used (we used SRM 2787 vs. samples from China), the time of exposure (3 h/d vs. 5 h/d) and different species (mice vs. rats).…”
Section: Discussioncontrasting
confidence: 99%
“…However, when we examined the effects of PM 10 exposure (500 μg/m 3 in a whole body exposure chamber) on tear secretion, no significant change in tear volume was observed after 2 weeks of exposure. Our results also differ from a recent study in female rats exposed to PM in an exposure chamber (500 μg/m 3 for 2 weeks) that showed a significant reduction in tear volume after 14 days [ 48 ]. These differences could be due to the type of particulates used (we used SRM 2787 vs. samples from China), the time of exposure (3 h/d vs. 5 h/d) and different species (mice vs. rats).…”
Section: Discussioncontrasting
confidence: 99%
“…Exposure of mice to fine particulate matter (PM2.5) resulted in dry eye syndrome, as evidenced by increased inflammation in the cornea and conjunctiva, increased tear film damage, the induction of apoptosis in corneal superficial and basal epithelium, and decrease in tear volume [ 60 ]. These results were consistent with results of other studies that found reductions in tear volume, increases in corneal irregularities, and decreases in stability of tear film due to deficits in the mucin-4 layer of the film in mice that were exposed to particulate matter [ 61 , 62 ]. Yang et al placed eye drops with increasing concentration of fine PM into the right eye of C57BL/6 mice and found a dose-dependent decrease in tear secretion and conjunctival goblet cells, consistent with findings in dry eye in humans [ 63 ].…”
Section: Pollution Effectssupporting
confidence: 93%
“…PM and gases routinely interact with exposed surfaces of the body such as the skin [ 39 , 40 ] and eyes [ 41 ] where they may be inflammatory. In the eyes, these pollutants can cause dryness and irritation [ 41 , 42 ] through oxidative stress [ 43 ], mucin disruption, and loss of microvilli, corneal and goblet cells [ 14 , 44 , 45 ]. In the airways, PM 2.5 can enter the alveoli where it induces inflammation and oxidative stress that may result in systemic immune mobilization [ 15 , 46 ].…”
Section: Discussionmentioning
confidence: 99%